2018
DOI: 10.3346/jkms.2018.33.e10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in Hospitalized Patients: a Multicenter Cross-sectional Study

Abstract: BackgroundMalnutrition is associated with many adverse clinical outcomes. The present study aimed to identify the prevalence of malnutrition in hospitalized patients in Korea, evaluate the association between malnutrition and clinical outcomes, and ascertain the risk factors of malnutrition.MethodsA multicenter cross-sectional study was performed with 300 patients recruited from among the patients admitted in 25 hospitals on January 6, 2014. Nutritional status was assessed by using the Subjective Global Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
3
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 32 publications
9
85
3
8
Order By: Relevance
“…In that study, the prevalence of malnutrition differed between age groups and was significantly higher in older patients (aged ≥70 years) than in the younger age group (38.2% vs 17.2%; P < .001). 31 Furthermore, the current study showed that patients with cancer between ages 51 and 64 years have >3 NIS more often than younger patients. We observed a higher risk for the occurrence of no appetite, problems swallowing, and dry mouth in older patients with cancer compared with those aged ≤50 years.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In that study, the prevalence of malnutrition differed between age groups and was significantly higher in older patients (aged ≥70 years) than in the younger age group (38.2% vs 17.2%; P < .001). 31 Furthermore, the current study showed that patients with cancer between ages 51 and 64 years have >3 NIS more often than younger patients. We observed a higher risk for the occurrence of no appetite, problems swallowing, and dry mouth in older patients with cancer compared with those aged ≤50 years.…”
Section: Discussionsupporting
confidence: 50%
“…In that study, with 300 patients recruited in 25 hospitals in Korea, the prevalence of malnutrition was 22%, as assessed by the Subjective Global Assessment. In that study, the prevalence of malnutrition differed between age groups and was significantly higher in older patients (aged ≥70 years) than in the younger age group (38.2% vs 17.2%; P < .001) …”
Section: Discussionmentioning
confidence: 74%
“…Previous research found that as many as 25%-35% of older adults lose at least one activity of daily living (ADL) following 10-14 days of hospitalization for acute illness, 1,2) 25% suffer cognitive functional decline after 10-14 days of hospitalization, 3,4) and 20%-25% experience emotional disturbances after discharge (chiefly depression and anxiety). 5,6) In addition, in 20%-40% of such patients, their nutritional status is worse than it was before hospitalization, [7][8][9] and all were at risk for falls after discharge. 10) However, the vast majority of patients discharged after acute care return home with no further care.…”
Section: Introductionmentioning
confidence: 99%
“…Many hospitals in South Korea supply PN in accordance with ASPEN and ESPEN guidelines. In South Korea, the prevalence of malnutrition in the hospitalized adult patients reportedly ranges from 22 to 61% [10,11]. However, the clinical practices and characteristics of current PN formulations for inpatients who receive PN are not known.…”
Section: Introductionmentioning
confidence: 99%